1977
DOI: 10.1002/art.1780200401
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical features in HLA‐B27 positive and negative patients with ankylosing spondylitis

Abstract: The clinical features of ankylosing spondylitis ( A S ) were compared in 63 HLA-B 27 positive ( + ) and 15 B27 negative ( -) individuals with this disease. There were no differences in age at onset, functional class, degree of deformity, pain, severity of X-ray changes, or frequency of peripheral joint involvement or of reconstructive orthopedic surgery. These data demonstrated that skeletal manifestations of AS were essentially the same in B27( +) and ( -) patients, and provide no evidence for the speculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
6
7

Year Published

1978
1978
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(85 citation statements)
references
References 9 publications
6
64
6
7
Order By: Relevance
“…Some recent clinical studies proved the relationship between HLA-B27 positivity and the early onset of symptoms; however, some studies reported a negative relationship (11,12). In the present study, there was no significant relationship between the age of disease onset and HLA-B27 positivity.…”
Section: Discussioncontrasting
confidence: 80%
“…Some recent clinical studies proved the relationship between HLA-B27 positivity and the early onset of symptoms; however, some studies reported a negative relationship (11,12). In the present study, there was no significant relationship between the age of disease onset and HLA-B27 positivity.…”
Section: Discussioncontrasting
confidence: 80%
“…In this study, HLA-B*2704 and HLA-B*2705 were the most prevalent HLA-B27 subtypes detected in the north Chinese AS patients, and this finding is consistent with findings of previous studies on Chinese patients with AS. 5,8,11 It has been reported that HLA-B*2704-positive patients had a significantly earlier onset of disease than that of HLA-B*2705-positive patients 10 but we did not find this difference in our study. Neither were there differences in disease activity between AS patients with B*2704 and B*2705.…”
Section: Discussioncontrasting
confidence: 90%
“…9 It was also reported that HLA-B27-positive AS patients are more likely to develop acute anterior uveitis than HLA-B27-negative ones as early as in 1977. 10 For the subtypes of HLA-B27, most subtypes are too rare to make any substantial statement about disease association, but the common subtypes of HLA-B27, B2702, B2704, and B2705 have all been AS Patients with B*2704 have More Uveitis than B*2705 67 associated with AS in previous studies. In this study, HLA-B*2704 and HLA-B*2705 were the most prevalent HLA-B27 subtypes detected in the north Chinese AS patients, and this finding is consistent with findings of previous studies on Chinese patients with AS.…”
Section: Discussionmentioning
confidence: 96%
“…However, patients with both antigens appeared to have extraarticular stigmata more frequently than the other groups, while patients with B27 seemed to develop more severe sacroiliitis radiographically. These findings must be interpreted with caution because of the small numbers within each group and because others have found no clinical or radiographic differences in B27-positive versus B27-negative patients with ankylosing spondylitis (31 ).…”
Section: Discussionmentioning
confidence: 74%